Men of our time [videorecording] Lenin - Cameron, James; Lagone, Patricia (Heroes and tyrants of the twentieth century series, 1990)
Lenin was a convict prophet, exile, conspirator, and one of the greatest revolutionary thinkers in human history. Heroes and tyrants recreates the path to glory of this leader who led the Bolshevik Revolution to become the founder of the Russian Communist Party and first head of the Soviet state. Reveals a ravaged and chaotic Russia and the fiery speeches of Lenin.